2005
DOI: 10.1016/j.rapm.2004.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased postpartum use of oral pain medication after a single dose of epidural morphine

Abstract: These results suggest that epidural morphine decreases the need for oral pain medication in the first 24 hours postpartum. No significant dose-dependent side effects were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
2
3
0
1
Order By: Relevance
“…Pain after vaginal delivery may result from episiotomy, perineal laceration or uterine involution. This is usually treated with oral medications [27]. Our results are compatible with reports showing the analgesic effect of music on postoperative patients.…”
Section: Discussionsupporting
confidence: 91%
“…Pain after vaginal delivery may result from episiotomy, perineal laceration or uterine involution. This is usually treated with oral medications [27]. Our results are compatible with reports showing the analgesic effect of music on postoperative patients.…”
Section: Discussionsupporting
confidence: 91%
“…The study of Macdonald and Smith 8 evaluated only women with episiotomies because the investigators thought that this degree of perineal trauma necessitated additional analgesia. The 2 largest studies 8,9 and our study had the highest quality (Ն4/5 Jadad score 11 ) and found a similar drug-sparing effect in the epidural morphine compared with saline groups. The 2 small studies* † reported only as abstracts did not find a reduction in maternal VAS pain scores during the first 24 h postpartum.…”
Section: Discussionsupporting
confidence: 60%
“…23 Addition of buprenorphine intrathecally or epidurally provides a good postoperative analgesia without prolonged motor block. 14,15 A study by Shaloo Ipe et al observed that 150mcg buprenorphine was not as effective as 300 mcg buprenorphine given epidurally where the duration of analgesia was highest, though the analgesic effect of buprenrphine given intrathecally was quite effective with 50% patients showing the effect for 6 hours. 16 Some investigators have demonstrated that by using buprenorphine alone epidurally, in doses of 1 to 4 mg, varying durations of pain relief ranging from 2.5 to 9 hours are observed.…”
Section: Discussionmentioning
confidence: 99%